Psychological Assessment of Control and Coping with Neuropathic Pain in the Lumbar Spine - Agata Kryszak; Zbigniew Czernicki; Damian Wiśniewski (Rehabilitacja Medyczna, 2021)
Background: Pain in the lumbar spine is an increasingly common problem, not only neurological or orthopaedic, but also psychological. In epidemiological studies on the prevalence of neuropathic pain, conducted in countries such as the United Kingdom, the United States France, and Brazil, it has been shown that the prevalence of chronic pain with neuropathic properties is estimated at 7-10%. Chronic neuropathic pain is more common in women (8% versus 5.7% in men) and in patients > 50 years of age (8.9% versus 5.6% in women < 49 years old). It most frequently concerns the lumbar region and lower limbs. However, in Germany, it has been revealed that 40% of all patients experience at least some features of neuropathic pain such as burning, numbness and/or tingling, especially those with chronic pain in the lumbar spine and radiculopathy. Chronic pain not only hinders a patient's daily life activities, but over time, it has negative impact on the patient's psyche: it reduces his/her well-being, causing anxiety, fear, helplessness, regret and even hostility. It should be emphasized that each of these reactions is an individual feature.